Development of Experimental Skills of Schoolchildren Necessary for Participation in Scientific Volunteering in the Implementation of Project Activities - Elena A. Alekhina (Открытое образование (Москва))
The purpose of the study is to develop the experimental skills of schoolchildren necessary for the implementation of volunteer activities in the research laboratory of systematics and ecology of invertebrates of Omsk State Pedagogical University (OmSPU) through the organization of project activities.Materials and methods. To achieve this goal, the author of the article analyzed the directions of scientific work in the research laboratory of systematics and ecology of invertebrates of OmSPU and the content of regulatory documents (the Federal State Educational Standard of basic general education and the Federal working program of basic general education in chemistry of the basic level). Based on the analysis, the experimental skills necessary for volunteering in the laboratory and the topics of the school course of chemistry of the 8th and 9th grade, in which the formation of these skills takes place, were identified. The entrance testing of the necessary knowledge and assessment of the development level of experimental skills among potential volunteers showed their insufficient formation and allowed students to participate in the work of the interdisciplinary project group of the Technopark of Universal Pedagogical Competencies of OmSPU named after V.M. Samosudov in order to develop the necessary knowledge and skills.Results. The results of the initial stage of the pedagogical experiment are presented, during which, with the help of testing, the availability of knowledge necessary for work in the laboratory was determined and the level of development of the necessary experimental skills was assessed according to the method of V. Vivyursky.The lack of knowledge and the lack of formation of the necessary experimental ones made it possible to proceed to the main stage of the pedagogical experiment, during which schoolchildren carried out project activities to study the composition and properties of water and soil in the residual lakes of the Zamaraika river. They presented the results of their project activities at the educational and research conference and were awarded with laureates’ diplomas.At the final stage of the pedagogical experiment, knowledge about the basics of conducting scientific research was retested and the level of necessary experimental skills was determined, as well as the statistical significance of the results was assessed using the Mann-Whitney U-test. The results showed an increase in the level of knowledge and skills of the students and allowed them to identify a tendency towards an increase in the value of the measured parameters and the opportunity for students to start participating in scientific volunteering at research laboratory of systematics and ecology of invertebrates of OmSPU.Conclusion. The main types of activities carried out in the scientific research laboratory of systematics and ecology of invertebrates of OmSPU, in which volunteers can participate, have been identified. Based on the analysis of regulatory documents, it has been established that students of 8-9 grades can be involved in work in the laboratory. The choice of activities that a volunteer can carry out is based on the Federal State Educational Standard of basic general education and the Federal working program of basic general education in chemistry (basic level). It has been established that the implementation of project activities by potential volunteers can contribute to the development of knowledge and the formation of experimental skills necessary in the course of scientific volunteering.